Preparation method and application of curcumin-loaded composite nanoparticles
By chelating metal calcium ions of curcumin-encapsulated nanoparticles by sodium alginate and carboxymethyl chitosan, combined with chemokinetic therapy, the problems of poor efficacy and low targeted delivery efficiency in liver cancer treatment are solved, and high efficiency is achieved. Targeted anti-tumor effects.
Patent Information
- Application Number
- CN202411335226.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
Existing liver cancer treatment methods such as chemotherapy and immunotherapy have poor efficacy and great toxic side effects, and the targeted delivery efficiency of nanomaterials in the tumor site is low, affecting the therapeutic effect.
Sodium alginate and carboxymethyl chitosan chelate metal calcium ions to form a double-skeleton structure that encapsulates curcumin and doped with manganese carbonate to prepare Cur@CMCS/SA-CaCO3/MnCO3 nanoparticles, using them to the acid tumor microenvironment The Chinese medicine is released, combined with chemokinetic therapy, and achieves targeted tumor treatment.
It significantly improves the drug loading rate and bioavailability of curcumin, enhances the inhibitory effect on liver cancer cells, achieves targeted and efficient anti-tumor treatment, and reduces side effects.
Smart Images

Figure CN119139268A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anticancer, and relates to a preparation method of composite nanoparticles loaded with curcumin and application thereof. Background Art
[0002] Primary liver cancer is the most common type of liver cancer, of which hepatocellular carcinoma accounts for about 90% of all liver cancer cases. Currently, the best options for advanced treatment are chemotherapy and immunotherapy, but immunotherapy has low bioavailability and high cost, while chemotherapy has tumor resistance, insufficient solubility and permeability, low bioavailability, and non-targetedness, resulting in poor overall efficacy. At the same time, the toxic side effects of these therapies cannot be ignored. Therefore, conducting active and effective research on liver cancer prevention and treatment and finding new anti-tumor drugs are currently urgent problems that need to be solved.
[0003] With the rapid development of nanotechnology, nanomaterials have received widespread attention in the field of modern medicine. In the emerging field of controlled drug release, nanomaterials have more advantages than traditional large-size drug carriers, mainly in terms of increasing drug loading, prolonging drug release time, and improving drug effectiveness. As an innovative and efficient tumor treatment strategy, nanomaterial kinetic therapy for tumors mainly uses nanocarriers as drug delivery systems, and achieves targeted drug delivery, controlled release, and responsive treatment of the tumor microenvironment by regulating the kinetic behavior of drugs in the body. Currently, the nanodynamic therapies used in tumor research mainly include photodynamic therapy, sonodynamic therapy, and chemodynamic therapy (CDT). Among them, chemodynamic therapy is driven by the Fenton reaction, mainly through Fe 2+ / Fe 3+ Redox, catalyzing intracellular hydrogen peroxide (H2O2) to produce highly toxic ROS. Compared with photodynamic therapy and sonodynamic therapy, it is not subject to the hypoxic conditions of the tumor microenvironment. It can produce reactive oxygen and oxygen in a controllable and unlimited tissue depth in response to high concentrations of hydrogen peroxide in the tumor microenvironment. Because it has few side effects and does not require exogenous energy, it has become an effective cancer treatment. Since tissues and cells are full of various electrolyte ions (such as calcium and phosphate) and bioactive groups, they may affect CDT by chelating with iron ions or reacting with hydroxyl radicals. Many studies have shown that the effectiveness of CDT in the treatment of cancer is often limited by the proportion of metal ions. It is necessary to supplement low-valent metal ions in the process of synthesizing nanomaterials to enhance the performance of CDT, which is also a key factor limiting the efficacy of CDT. At the same time, in the case of targeted delivery of nanomaterials, the delivery efficiency of tumor sites and the problem of universal distribution in all organs are still very difficult challenges.
[0004] As a traditional Chinese medicine chemotherapy agent, curcumin is a polyphenol extracted from the rhizome of turmeric, which has multiple biological activities such as anti-tumor, anti-proliferative, anti-metastatic, anti-angiogenic, anti-inflammatory, and antioxidant. Its anti-tumor effects involve multiple mechanisms, such as regulating pro-apoptotic and anti-apoptotic proteins, growth factors, enzymes, inhibiting STAT3 and NF-κB signaling pathways, reducing the production of inflammatory mediators, and inhibiting angiogenic cytokines. Despite these health benefits, the use of free curcumin as a therapeutic drug is limited due to its hydrophobicity, resulting in poor water solubility, rapid metabolism and systemic clearance, especially in the intestine and liver. In order to overcome these limitations by improving the solubility and bioavailability of curcumin, nanomedicine technology can achieve a transformation in its application limitations, and nanoparticles loaded with curcumin can become the key to overcome the undesirable properties of curcumin in the future.
[0005] In recent years, rapid progress has been made in the material science and nanoparticle design related to chitosan-based cancer nanomaterials, and great research progress has been made in improving the pharmacokinetics and pharmacodynamics of drugs. Chitosan is a biotechnological derivative of chitin and has a wide range of applications in the pharmaceutical and biomedical fields. However, chitosan is insoluble in water, which greatly limits its application. By chemically modifying and introducing hydrophilic groups, a water-soluble chitosan derivative, carboxymethyl chitosan, can be obtained. Compared with chitosan, carboxymethyl chitosan has significantly improved water solubility and can be dissolved in a wide range of pH solutions. It is non-toxic and tasteless and has good biocompatibility. It can be used to encapsulate and deliver cancer therapeutic drugs with pH-dependent solubility, and endow them with the ability to target the tumor microenvironment and anti-cancer activity.
[0006] Alginate is a natural polysaccharide extracted from brown seaweed and bacteria. It has the characteristics of biocompatibility, biodegradability, non-toxicity, and easy gelation. It can be processed into various forms of hydrogels, microspheres, fibers and sponges, and has a wide range of applications in the biomedical field. Among them, sodium alginate is one of the most widely studied alginate derivatives in the pharmaceutical and biomedical fields. Sodium alginate can be combined with other biopolymers, and by chemically or physically cross-linking and fixing specific molecules such as sugar molecules and peptides, various properties and structures such as biodegradability, gelation, mechanical strength and high cell affinity can be obtained. At present, nanoparticles composed of sodium alginate have become one of the most widely used characteristic biomaterials for drug delivery and targeted drug delivery. In addition, sodium alginate can be combined with divalent metal ions such as Ca 2+ A stable eggshell-like structure is formed, and the cross-linking with carboxymethyl chitosan strengthens the cross-linked network of the hydrogel polymer, reduces the porosity, and can load high doses of curcumin and control its release by adjusting the network cross-linking density, which is beneficial to the stability and sustained release effect of the encapsulated drug.
[0007] Currently, there are no reports on the preparation method of composite nanoparticles loaded with curcumin and their application in the treatment of liver cancer. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing composite nanoparticles loaded with curcumin and its application in view of the above problems, and to synthesize a Cur@CMCS / SA-CaCO3 / MnCO3 nanoparticle that is a double skeleton of sodium alginate and carboxymethyl chitosan chelating metal calcium ions to encapsulate curcumin and doped with manganese carbonate. The double skeleton structure of natural hydrogel / calcium carbonate not only overcomes the poor water solubility and low bioavailability of curcumin, but also improves the drug loading rate. The dense calcium shell structure is also acid-responsive and can specifically disintegrate and release drugs in the acidic tumor microenvironment. The nanoparticles showed significant cytotoxicity and inhibitory effects on human liver cancer cells HepG2, and could effectively induce cell apoptosis. Its anti-tumor effect was better than that of the curcumin treatment group alone. In order to achieve the above object, the technical solution adopted by the present invention is: The preparation method of composite nanoparticles loaded with curcumin comprises the following steps: (1) Sodium alginate and chitosan were mixed in a proportion and added into a flat-bottom flask, and 200 mL of sodium carbonate solution with a pH of 7.5-8 was prepared and added, and stirred; (2) Then wrap the flat-bottom flask with aluminum foil, add curcumin and stir, and add an appropriate amount of phosphate buffer with pH = 5.8 to adjust the pH of the system in the flask to 7.0; (3) Then, under stirring, 15 mL of calcium chloride solution was added dropwise, followed by slow dropwise addition of 160 μL of manganese chloride solution, while continuing to stir; (4) Then add 7.5 mL of sodium carbonate solution dropwise and continue stirring; (5) The solution in the flat-bottom flask is then centrifuged, the supernatant is discarded, the precipitate is collected, and the precipitate is resuspended in phosphate buffer to prepare a suspension to obtain the composite nanoparticles loaded with curcumin for later use.
[0009] In the present invention, the ratio of sodium alginate to chitosan in step (1) is 200.0 mg:100.0 mg; the concentration of the sodium carbonate solution is 0.1 mol / L; and the stirring is carried out on a magnetic stirrer at 850 rpm for 20 seconds.
[0010] In the present invention, the amount of curcumin in step (2) is 1 / 10 of that of chitosan; the stirring is carried out on a magnetic stirrer at room temperature in the dark, and the stirring condition is stirring at 850 rpm for 24 hours.
[0011] In the present invention, the calcium chloride solution and the manganese chloride solution in step (3) are both added dropwise using a separatory funnel at a flow rate of 1.5 mL / min; the concentration of the calcium chloride solution is 50 mmol / L; and the stirring is performed on a magnetic stirrer at room temperature in the dark at 800 rpm for 4 h.
[0012] In the present invention, the sodium carbonate solution in step (4) is added dropwise using a 1000 μL single-channel pipette; the solubility of the sodium carbonate solution is 0.1 mol / L; and the stirring is performed on a magnetic stirrer at room temperature in the dark at 800 rpm for 1 hour.
[0013] In the present invention, the centrifugation in step (5) is performed at 5000 rpm on a desktop centrifuge for 10 min.
[0014] Another object of the present invention is to provide a composite nanoparticle material loaded with curcumin prepared by the preparation method.
[0015] Another object of the present invention is to provide an application of the composite nanoparticle material loaded with curcumin prepared by the preparation method in the preparation of drugs for treating liver cancer.
[0016] Due to the adoption of the above technical solution, the present invention has the following beneficial effects: The present invention provides a composite nano-platform Cur@CMCS / SA-CaCO3 / MnCO3, which is synthesized by using a novel sodium alginate, carboxymethyl chitosan chelated with calcium carbonate and doped with manganese carbonate to form a double skeleton structure to encapsulate curcumin for the treatment of liver cancer. The double skeleton structure is made by utilizing the characteristics of sodium alginate and carboxymethyl chitosan that stably bind with calcium metal ions to successfully encapsulate the poorly water-soluble and low-bioavailability chemotherapy drug curcumin and successfully deliver it to tumor tissues. At the same time, its dense calcium carbonate shell has pH responsiveness and can specifically disintegrate and release drugs in the acidic tumor microenvironment. The released curcumin, Mn 2+ , Ca 2+ They play different anti-tumor effects. Curcumin as a chemotherapeutic drug can not only inhibit Ca 2+ Through the plasma membrane, the released exogenous Ca 2+ Accumulation in the cytoplasm cooperates with the increase of endogenous cellular calcium ion accumulation to further lead to apoptosis, and can also downregulate the expression of pro-inflammatory factors to exert anti-inflammatory effects. 2+ Able to induce chemodynamic therapy. The construction of the Cur@CMCS / SA-CaCO3 / MnCO3 nanoplatform can combine chemotherapy and chemodynamic therapy to treat liver cancer, and organically combine multiple components with apoptosis-inducing effects to achieve efficient treatment of targeted cancer. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1Example 1 of the present invention A is the dynamic light scattering result of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles dissolved in water; B is the Zeta potential result of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles; C is the TEM image of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles (the scales from left to right in Figure C are 500nm, 200nm, 100nm, and 50nm, respectively); D is the EDS element of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles Surface scanning analysis (scale = 50 nm); E is the EDS element point scanning spectrum of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles; F is the infrared absorption spectrum of Cur@SA / CMCS-CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3 and Cur; G is the TG curve of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles; H is the cumulative release curve of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles in PBS curves of different pH.
[0018] Figure 2 Example 1 of the present invention A is the protein adsorption capacity of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles (n=3); B is the hemolysis of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles (n=3); CD are the survival rates of HUVEC cells (C) (n=6) and HepG2 cells (D) (n=6) after treatment with different concentrations of Cur@SA / CMCS-CaCO3 / MnCO3, P<0.0001; E is the live-death fluorescence imaging of HepG2 cells after co-incubation with different materials (scale bar=100μm); F is the in vitro uptake of HepG2 cells after co-incubation with different materials (scale bar=100μm); G is the double staining of lysosomes and calcium ions of HepG2 cells after co-incubation with different materials (scale bar=100μm).
[0019] Figure 3 A is the effect of HepG2 tumor cell migration after co-incubation with different materials (scale bar = 100 μm) and its quantification (B); C is the clone formation experiment of HepG2 tumor cells after co-incubation with different materials (scale bar = 5 mm) and its quantification (D).
[0020] Figure 4A is the ROS content of HepG2 tumor cells after co-incubation with different materials (scale = 100 μm); B. Mitochondrial membrane potential of HepG2 tumor cells after co-incubation with different materials (scale = 50 μm); C is the co-localization of mitochondria and calcium ions of HepG2 tumor cells after co-incubation with different materials (scale = 100 μm); D is the expression of Bcl-2 and Caspase-3 in HepG2 tumor cells after co-incubation with different materials.
[0021] Figure 5 The in vitro antitumor effect of Cur@CMCS / SA-CaCO3 / MnCO3 nanoparticles. (A) Construction and treatment of HepG2BALB / c mouse model; (B) Tumor growth curve of mice in different treatment groups, n=6; (C) Average weight change of mice during treatment; (D) Photos of mouse tumor resection on day 14; (E) Statistical analysis of tumor weight resection of mice in each group, n=6; (F) 40-day survival curve of mice, n=7; (G) Organ coefficients of main organs (heart, liver, spleen, lung and kidney) of mice in different treatment groups; (H) H&E staining of tumor tissues in different treatment groups, scale: 100μm; (I) TUNEL staining of tumor tissues in different treatment groups, scale: 50μm; (J) Ki-67 staining of tumor tissues in different treatment groups, scale: 50μm.
[0022] Figure 6 This is the in vitro anti-tumor mechanism of Cur@CMCS / SA-CaCO3 / MnCO3 nanoparticles. (A) Von Kossa results of tumor tissue sections in different treatment groups, scale: 50μm; (B) ROS staining confocal fluorescence imaging of tumor sections in different treatment groups, scale: 50μm; (CE) Confocal fluorescence imaging of apoptosis key pathway proteins Bcl-2, Caspase-9 and Cleaved Caspase-3 fluorescent immunohistochemical staining of tumor sections in different treatment groups, scale: 50μm; (F) Immunoblotting analysis of the content of Bcl-2, Bax, Caspase-9 and Cleaved Caspase-3, key proteins in the apoptosis pathway of tumor tissues in different treatment groups; (GJ) Quantification results of grayscale values of bands in Western blot experiments, n=3; (KL) ELISA method to detect the content of pro-inflammatory factors IL-6 and TNF-α in mouse serum, n=4.
[0023] Figure 7 These are photographic comparisons of the conditions of BALB / c mice in different treatment groups on days 0, 4, 8, and 12 of treatment.
[0024] Figure 8 These are H&E stained microscope images of the main organs (heart, liver, spleen, lung, and kidney) of BALB / c mice in different treatment groups. Scale bar: 100 μm.
[0025] Fig. 9 A is the quantitative image of TUNEL staining in tumor tissues of different treatment groups; Fig. 9 B Quantification of Ki-67 staining in tumor tissues of different treatment groups.
[0026] Fig.10 It is the quantitative image of ROS staining in tumor tissues of different treatment groups.
[0027] Fig.11 A is the quantification result of Bcl-2 protein fluorescent immunohistochemistry in tumor sections of different treatment groups; B is the quantification result of Caspase-9 protein fluorescent immunohistochemistry in tumor sections of different treatment groups; C is the quantification result of CleavedCaspase-3 protein fluorescent immunohistochemistry in tumor sections of different treatment groups.
[0028] In the above figure, * indicates P<0.05, ** indicates P<0.01, and *** indicates P<0.001. DETAILED DESCRIPTION
[0029] The specific implementation of the invention is further described below with reference to the accompanying drawings.
[0030] Example 1 The preparation method of composite nanoparticles loaded with curcumin comprises the following steps: (1) Weigh 200 mg of sodium alginate and 100 mg of chitosan on an analytical balance and pour into a 500 mL flat-bottom flask. Pour 200 mL of 0.1 mol / L Na2CO3 solution with a pH of 7.5-8.0 into the 500 mL flat-bottom flask and stir at 850 rpm on a magnetic stirrer for 20 s. (2) The flat-bottom flask was then wrapped with aluminum foil, 10 mg of curcumin was weighed on an analytical balance under light-proof conditions, and stirred on a magnetic stirrer at 850 rpm for 24 h at room temperature and light-proof conditions, and an appropriate amount of phosphate buffer with a pH of 5.8 was added to adjust the pH of the system in the flask to 7.0; (3) Then, under stirring conditions, 15 mL of 50 mmol / L calcium chloride solution was added dropwise using a separatory funnel at a flow rate of 1.5 mL / min, followed by the addition of 160 μL of manganese chloride solution dropwise using a separatory funnel at a flow rate of 1.5 mL / min, and stirred at 800 rpm for 4 h at room temperature in the dark; (4) Then, 7.5 mL of 0.1 mol / L sodium carbonate solution was added dropwise using a 1000 μL single-channel pipette, and stirring was continued at 800 rpm for 1 h at room temperature in the dark; (5) The solution in the flat-bottom flask was then centrifuged at 5000 rpm for 10 min using a desktop centrifuge, the supernatant was discarded, the precipitate was collected, and resuspended in phosphate buffer to prepare a suspension to obtain the composite nanoparticles loaded with curcumin (Cur@SA / CMCS-CaCO3 / MnCO3), which was set aside.
[0031] Example 2: In this example, the Cur@SA / CMCS-CaCO3 / MnCO3 nanomaterial prepared in the example of this application was physically and chemically characterized by: After Cur@CMCS / SA-CaCO3 / MnCO3 was diluted to an appropriate multiple, the material was ultrasonicated (60w, 15min) using an ultrasonic crusher. After it was evenly dispersed, the hydrated particle size and Zeta potential of the nanoparticles were observed using a nanoparticle size potentiometer.
[0032] like Figure 1 As shown in A, the effective particle size distribution of Cur@SA / CMCS-CaCO3 / MnCO3 measured by nanoparticle size analyzer is around 220nm. Figure 1 As shown in B, the potential of Cur@SA / CMCS-CaCO3 / MnCO3 is mainly between -20mV and -30mV, which is a negative potential. Since the greater the absolute value of the potential of the drug delivery system, the more stable the system is, it can be considered that Cur@SA / CMCS-CaCO3 / MnCO3 is relatively stable; in addition, considering that most proteins and cell membrane surfaces are naturally negatively charged, the negative charge of the nano drug delivery particles helps to reduce the adsorption of serum proteins, thereby increasing the circulation time in the blood. Figure 1 The contents of carbon, oxygen, sodium, calcium, and manganese in Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles shown in E are 43.39%, 38.50%, 5.88%, 6.81%, and 2.48%, respectively. These elements are evenly distributed on the Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles, which helps to prove the composition of the nanoparticles, indicating that Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles may contain sodium alginate, carboxymethyl chitosan, and inorganic components of calcium and manganese. Figure 1 As shown in F, it is preliminarily inferred that Cur@SA / CMCS-CaCO3 / MnCO3 nanospheres contain the same components as SA / CMCS-CaCO3 / MnCO3 and Cur. Figure 1G shows the TG curve of Cur@SA / CMCS-CaCO3 / MnCO3. In a nitrogen atmosphere, a constant temperature increase strategy of 10°C per minute was used for heating measurement, and the temperature range was set from 30°C to 800°C. Since CaCO3 and MnCO3 are inorganic components, the observed mass reduction is mainly attributed to the decomposition of macromolecular substances SA, CMCS and polyphenols Cur. Based on this, it can be estimated that the water content in Cur@SA / CMCS-CaCO3 / MnCO3 is approximately 8.30%, while the total content of CaCO3 and MnCO3 is approximately 63.94%. Figure 1 H shows the cumulative release curve of the chemotherapeutic drug Cur released from the Cur@SA / CMCS-CaCO3 / MnCO3 nanodrug delivery system under different pH environments (5.5, 6.5, and 7.4). When the pH values are 5.5 and 6.5, the release rates of Cur within 48 hours reach 52.43% and 64.78%, respectively, especially at pH 5.5. The release is more significant, indicating that the drug release rate of Cur@SA / CMCS-CaCO3 / MnCO3 in an acidic environment accelerates with the increase of acidity. In an environment simulating a physiological pH value of 7.4, the cumulative release of Cur reaches 33.97% in 36 hours, indicating that Cur@SA / CMCS-CaCO3 / MnCO3 is relatively stable under physiological conditions and can effectively reduce the premature leakage of drugs in the body. These results show that the Cur@SA / CMCS-CaCO3 / MnCO3 nanodrug delivery system has good pH responsiveness and can accelerate the release of drugs when reaching the tumor site, thereby improving its anti-tumor effect.
[0033] Example 3: This example is an in vitro anticancer test on the Cur@SA / CMCS-CaCO3 / MnCO3 nanomaterial prepared in the example of this application, including the following studies: (1) Drug release performance test of Cur@SA / CMCS-CaCO3 / MnCO3 In order to obtain the in vitro drug release profile of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles, dialysis was used in this paper. Pretreatment of dialysis bags: Dialysis bags with a molecular weight cutoff of 8000Da were cut into 10cm long sections and boiled in a 500mL beaker for 10min. Before dialysis, the inside and outside of the dialysis bag were thoroughly cleaned with distilled water. Subsequently, a 0.5mg / mL concentration of Cur@SA / CMCS-CaCO3 / MnCO3 suspension was loaded into the dialysis bag. Each dialysis bag was filled with the same amount of suspension and ensured that the dialysis bag was completely immersed in 30mL PBS release buffer containing different pH values (7.4, 6.5, 5.5). Cur entered these release media through the dialysis bag. At the same time, in order to promote drug release, 25% ethanol was added to the release medium. By using a magnetic stirring water bath with digital thermostatic control, we simulated the drug release process under constant temperature conditions of 150rpm and 37℃. At 1, 2, 4, 8, 12, 24 and 36h, 2mL of release medium was extracted for testing, and then an equal amount of isothermal release medium was added to maintain the stability of the system. The concentration of Cur in the samples at each time point was measured by UV spectrophotometer in the wavelength range of 200-800nm with a scanning step of 1nm, so as to calculate the drug release rate under different pH conditions.
[0034] (2) Protein adsorption experiment of Cur@SA / CMCS-CaCO3 / MnCO3 Take 0.5mL of 500μg / mL BSA solution and mix with 0.5mL of 100μg / mL Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 respectively, and the protein concentration is 250μg / mL. Incubate at 37℃ in a constant temperature shaker for 1h, 4h, and 8h respectively. After incubation, centrifuge at 12000rpm for 10min.
[0035] This experiment uses a bicinchoninic acid (BCA) kit to evaluate the adsorption performance of nanoparticles on proteins. Prepare BCA working solution: Mix BCA reagent A and BCA reagent B in a volume ratio of 50:1, and ensure that the solution is mixed evenly. Next, take 20μL of supernatant from each sample and place it in a 96-well plate, setting up three replicate wells for each sample. Add 100μL of pre-prepared BCA working solution to each well; at the same time, add 20μL of standard protein solutions of different concentrations to the plate as a control. After incubating the 96-well plate in a 37°C incubator for 30 minutes, measure the absorbance of the sample and standard protein solution at a wavelength of 570nm. By drawing a protein standard curve, calculate the concentration of protein in the sample and compare it with the initial concentration of 250μg / mL to determine the amount of protein adsorbed by different nanomaterials.
[0036] (3) Hemolysis experiment of Cur@SA / CMCS-CaCO3 / MnCO3 5 mL of mouse blood was drawn and mixed with sodium heparin in the anticoagulation tube for anticoagulation. The mouse blood was washed with sterile PBS buffer solution at pH 7.4, gently mixed and resuspended, and centrifuged at 2000 rpm for 10 min. The red transparent supernatant was discarded, and this operation was repeated until the supernatant had no obvious red color and the sediment at the bottom of the tube was pure red blood cells. Red blood cell suspension: 200 μL of pure red blood cells were drawn and diluted to 10 mL with PBS for use. 0.5 mL of red blood cell suspension was mixed with 0.5 mL of 100 μg / mL Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3, 0.5 mL of sterile PBS buffer solution at pH 7.4 (negative control group), and 0.5 mL of ultrapure water (positive control group) in a 1.5 mL centrifuge tube. The centrifuge tube was placed in an incubator at 37°C for 4 hours, and then centrifuged for 10 minutes at 2000 rpm using a desktop centrifuge. The absorbance of the supernatant after centrifugation was then measured at a wavelength of 570 nm using an ELISA reader.
[0037] Hemolysis rate = (OD 实验组 -OD 阴性对照组 ) / (OD 阳性对照组 -OD 阴性对照组 )×100% Hemolysis is defined as a hemolysis rate exceeding 5%.
[0038] (4) Cytotoxicity of Cur@SA / CMCS-CaCO3 / MnCO3 The CCK-8 method was used to study the in vitro cytotoxicity of the nanodelivery system Cur@SA / CMCS-CaCO3 / MnCO3 on HepG2 cells.
[0039] HepG2 cells in good condition were used, and 5000 cells were inoculated in each well of a 96-well cell culture plate. The cells were cultured in a 5% CO2 cell culture incubator at 37°C until the cells were completely attached. Serum-free DMEM medium was used to prepare Cur@SA / CMCS-CaCO3 / MnCO3 to a concentration gradient of 0, 5, 10, 15, 25, and 35 μg / mL. After drug treatment, the cells were cultured in a 5% CO2 cell culture incubator at 37°C for 24 hours, the old culture medium was discarded, and 10 μL of CCK-8 solution and 90 μL of serum-free DMEM culture medium were added to each well on the clean bench. Incubate in a 37°C, 5% CO2 incubator for 2 hours. The absorbance value of the well to be tested was measured at 490 nm using a full-wavelength microplate reader. Finally, the survival rate of the cells in each experimental group was calculated.
[0040] The formula is as follows: Cell viability = (OD 实验组 -OD 空白组 ) / (OD 对照组 -OD 空白组 )×100% The blank control group was a well without cells, and the negative control group was a well with cells but without drug treatment.
[0041] (5) Live and dead cell staining In the center of each well of a 6-well plate, drop 100 μL of PBS to prevent the cell slide from sliding. Place a cell slide of appropriate size and place 5×10 5 HepG2 cells with good growth status were added at a concentration of 100 μg / well and cultured overnight. After overnight culture until adherence, serum-free DMEM medium containing Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 at a drug concentration of 25 μg / mL was added for 6 hours, and PBS was used as a control. 24 hours after administration, the staining working solution was prepared with Calcein-AM and PI, and the cells were stained for 15 minutes in the dark. After 15 minutes, the staining solution was removed and washed twice with PBS, each time for 2 minutes. The cell slide was taken out in the dark, 10 μL of anti-fluorescence quencher was added, and after sealing, the fluorescence images of cell live and dead staining were collected using an inverted fluorescence microscope.
[0042] (6) Cellular uptake In the center of each well of a 6-well plate, drop 100 μL of 1× PBS to prevent the cell slide from sliding. Place a cell slide of appropriate size and place 2×10 5HepG2 cells with good growth status were added at a concentration of 100 μg / well and cultured overnight. After culturing until adherence, serum-free DMEM medium containing Cur, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 at a drug concentration of 25 μg / mL was added for 1, 4, and 6 hours, and PBS was used as a control. Since Cur is naturally fluorescent, no fluorescent labeled drugs are required in this experiment. After staining, the dye solution was removed and washed twice with PBS, each time for 2 minutes. After fixing the cells with 4% paraformaldehyde solution, the cell slides were removed, 10 μL of DAPI anti-fluorescence quencher was added, and after sealing, the cells were collected using an inverted fluorescence microscope to capture the uptake of nanoparticles.
[0043] (7) Lysosomal calcium double staining experiment In the center of each well of a 6-well plate, drop 100 μL of PBS to prevent the cell slide from sliding. Place a cell slide of appropriate size and place 2×10 5 HepG2 cells with good growth status were added at a concentration of 100 / well and cultured overnight. After overnight culture until adherence, 25μg / mL of Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS, and Cur@SA / CMCS-CaCO3 / MnCO3 serum-free DMEM culture medium were added for 6h, and PBS was used as a control. Because the serum in the culture medium contains esterases that will cause Fluo-4 AM to decompose into Fluo-4, and phenol red will cause the fluorescence background to increase, it was washed with PBS twice, 2min each time, to remove the esterase and phenol red in the old culture medium. Stain with Fluo-4 AM (calcium ion fluorescent probe, 2mM) for 30min, aspirate the staining solution, and wash with PBS twice, 2min each time. Then use lysosomal red fluorescent probe to stain for 30min, aspirate the staining solution, and wash with PBS twice, 2min each time. The cells were fixed with 4% paraformaldehyde solution, and finally the cell slides were taken out, 10 μL of anti-fluorescence quencher was added, and after sealing, the fluorescence images of the cells taking up nanoparticles were collected using an inverted fluorescence microscope.
[0044] (8) Clone formation HepG2 cells with good growth were digested with 0.25% trypsin and inoculated into 6-well cell culture plates at 800 cells per well. They were gently mixed to make them evenly distributed in the wells. After overnight culture until adherence, 25 μg / mL of Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 serum-free DMEM medium were added. PBS was used as a control and the treatment was 24 hours. After 7 days of continued culture, the old culture medium was discarded and washed with PBS, and then the cells were fixed with 4% paraformaldehyde solution. In the staining step, the cells were stained with 0.1% crystal violet and washed again with PBS. After completing the above steps, the experimental results were observed, photographed and analyzed.
[0045] (9) Cell scratch HepG2 cells that were growing well were digested and plated at 2×10 5 Cells were inoculated into 12-well cell culture plates with 2-well wound healing plugs. When the cells adhered to the wall and reached a confluency of about 100%, the plugs were removed and washed with PBS three times. Serum-free medium containing 25 μg / mL Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 was added for 12 hours, and PBS was used as a control. The growth of tumor cells at the edge of the scratch was observed after 0, 24 and 48 hours. The experimental results were observed and photographed.
[0046] (10) Intracellular ROS production In the center of each well of a 6-well plate, drop 100 μL of PBS to prevent the cell slide from sliding. Place a cell slide of appropriate size and place 2×10 5 HepG2 cells with good growth status were added at a concentration of 100 cells / well and incubated overnight. After overnight culture until adherence, 25μg / mL of Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 serum-free medium were added for 6h, and PBS was used as a control. 20μM DCFH-DA DMSO solution was used for staining for 30min, the staining solution was aspirated, and the cells were washed twice with PBS, each for 2min. The cells were fixed with 4% paraformaldehyde solution, and finally the cell slides were taken out, 10μL of anti-fluorescence quencher was added, and after sealing, the cells were collected using an inverted fluorescence microscope to observe the DCFH-DA green fluorescence at 488nm excitation and 520nm emission bands.
[0047] (11) Mitochondrial membrane potential and mitochondrial calcium colocalization In the center of each well of a 6-well plate, drop 100 μL of PBS to prevent the cell slide from sliding. Place a cell slide of appropriate size and place 2×10 5 HepG2 cells with good growth status were added at a concentration of 100 μg / well and incubated overnight. After overnight culture until adherence, 25 μg / mL of Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 serum-free medium were added for 12 hours, and PBS was used as a control. After 12 hours, the cells were washed twice with PBS, each time for 2 minutes. They were stained with 2 μM JC-1 dye solution for 20 minutes. They were washed twice with PBS, each time for 2 minutes. After staining, the fluorescence intensity of JC-1 monomer and JC-1 polymer of the sample was observed under a fluorescence microscope. Photos were taken and recorded. When detecting JC-1 monomer, the excitation light was set to 490 nm and the emission light was set to 530 nm; when detecting JC-1 polymer, the excitation light was set to 525 nm and the emission light was set to 590 nm.
[0048] In order to prove that the decrease of mitochondrial membrane potential is related to mitochondrial calcium overload, the mitochondrial Ca2+ in cells after treatment with different groups was measured. 2+ In a 6-well plate, drop 100 μL of PBS into the center of each well to prevent the cell slide from sliding. Place a cell slide of appropriate size and place 2×10 5 HepG2 cells with good growth status were added at a concentration of 100 cells / well and incubated overnight. After overnight culture until adherence, 25μg / mL of Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 serum-free medium were added for 12 hours, and PBS was used as a control. After 12 hours, the cells were washed twice with PBS, each time for 2 minutes. Then, the mitochondrial fluorescent probe Mito Red and the calcium ion fluorescent probe Fluo-4 AM were prepared into a staining working solution. The cells after different treatments were stained for 30 minutes. After staining, the staining solution was aspirated and washed twice with PBS, each time for 2 minutes. After fixing the cells with 4% paraformaldehyde solution, the cell slides were taken out and observed and photographed under a fluorescence microscope.
[0049] Detection of apoptosis-related protein expression HepG2 cells were cultured in T75 culture flasks. After the cells were cultured until adherent, they were treated with Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 at a concentration of 25 μg / mL. After 24 hours of treatment, the cells were washed twice with PBS for 2 minutes each time.
[0050] Extract protein: Prepare cell lysis working solution with RIPA cell lysis buffer and PMSF protease inhibitor in a volume ratio of 100:1, and use it immediately. Mix the cells and cell lysis buffer and lyse the cells in an ice bath for 30 minutes. In order to avoid trypsin degradation of the target protein to be extracted, choose to scrape the cells with a cell scraper instead of using trypsin to digest the cells. Collect the cell solution after lysis and centrifuge it at 4℃12000rpm for 10 minutes, and immediately aspirate the supernatant into a pre-cooled centrifuge tube. The supernatant is the total protein solution.
[0051] Total protein detection: Use the BCA kit to prepare the BCA working solution according to the specific number of samples, that is, mix reagent A and reagent B in a ratio of 50:1 to ensure full mixing. For each protein sample, take 1μL of sample and place it in a 96-well plate, add 19μL of PBS buffer solution, and then add 100μL of freshly prepared BCA working solution to each well; at the same time, prepare a standard curve using the standard protein solution. Incubate the well plate at 37°C for 30min, and use an enzyme reader to measure the absorbance value at a wavelength of 570nm. Calculate the total protein concentration in the sample based on the absorbance value of the sample and the standard curve.
[0052] Protein denaturation: First, mix 5× reduced protein loading buffer with the protein solution at a ratio of 4:1, and then treat it in a boiling water bath for 15 minutes to complete the denaturation. After completion, place the sample in a refrigerator at -20℃ for subsequent use.
[0053] Glue preparation and sample loading: After cleaning, the glass plate for gel preparation is dried and cooled, and fixed on the gel preparation device. Prepare 12.5% separation gel, add TEMED to mix evenly, and then pour it into the glass plate for gel preparation. Next, slowly add pure water to the surface of the separation gel until it is full, and let it polymerize at room temperature for 30 minutes; after about 30 minutes, once the separation gel is solidified, remove the surface moisture and use absorbent paper to remove the remaining moisture. Then prepare 5% concentrated gel, add TEMED and stir quickly and evenly, and cover it on the separation gel. Fill the concentrated gel to the reserved space and insert the comb to ensure that there are no bubbles at the bottom of the comb. After the concentrated gel is solidified, carefully remove the gel preparation device and comb to prevent damage to the gel and prepare to enter the electrophoresis stage; place the gel preparation device in the electrophoresis tank, and inject sufficient electrophoresis buffer for sample loading, and avoid bubbles when loading. Set the concentrated gel voltage to 90V and the separation gel voltage to 150V. Stop electrophoresis when the bromophenol blue mark is about 1cm from the bottom and prepare for transfer.
[0054] Transfer: First prepare six clean thick filter papers and a PVDF membrane (thickness 0.45μm) of a size that matches the gel, and use methanol to activate the PVDF membrane for 2 minutes. Place the transfer clip, two sponges, filter paper, and activated PVDF membrane in the container containing the transfer solution. Next, unfold the transfer clip and place a sponge and three layers of filter paper on each side. Use a scraper to gently move the separated gel to the top of the filter paper, and then press the PVDF membrane against the gel, making sure there are no air bubbles between the two. Cover with another three layers of filter paper and remove air bubbles, and finally add a layer of sponge. Set the transfer conditions to a constant current of 300mA and a time of 30min. Cool the device by placing it in ice water during the transfer process.
[0055] Antibody incubation: First, transfer the PVDF membrane to an incubation box containing 1×TBST and wash on a shaker for 5 minutes. Next, gently add the rapid blocking solution to the incubation box, taking care to avoid pouring directly onto the membrane. Place the incubation box on a shaker at room temperature and block with the rapid blocking solution for 30 minutes; after the blocking process is completed, discard the blocking solution in the incubation box, add the primary antibody diluted with the primary antibody diluent, and then place the incubation box on a shaker at 4°C overnight, set to slow shaking. After that, recover the primary antibody and wash the membrane three times quickly on a shaker with TBST, each for 5 minutes. After the secondary antibody is diluted to a ratio of 1:5000 with TBST, add it to the incubation tank and incubate it on a shaker at room temperature with slow shaking for 30 minutes. Finally, wash the membrane three times quickly with TBST, each for 5 minutes.
[0056] Chemiluminescence: First, mix the two liquids of reagent A and reagent B in the ECL kit in a 1:1 ratio. After taking the PVDF membrane out of the incubation tank, gently remove the droplets remaining on the surface, and then completely immerse it in the prepared ECL luminescent solution for 1 minute. Then, gently remove the excess luminescent solution on the surface of the membrane and place the membrane in the chemiluminescence detector to avoid bubbles. Perform the chemiluminescence process according to the set program, and take photos and record after the exposure is completed.
[0057] (12) Statistical analysis The data of this study were statistically processed by Origin 8.0 software. All experiments were repeated at least three times, and the results were presented as mean ± standard deviation (SD). The experimental data were analyzed by variance analysis (ANOVA). If there was a statistically significant difference between the two groups of data, it was marked as *P<0.05; if the difference was significant, it was marked as **P<0.01; if the difference was relatively significant, it was marked as ***P<0.001; if the difference was extremely significant, it was marked as ****P<0.0001. (13) Results like Figure 2As shown in A, the adsorption of protein by Cur@SA / CMCS-CaCO3 / MnCO3 nanomaterials did not change significantly over time. Figure 2 B shows that the red blood cells in the negative control group and all experimental groups were deposited at the bottom of the test tube after centrifugation, leaving the supernatant clear and colorless; in contrast, the supernatant of the positive control group showed a distinct red color after centrifugation, indicating that the red blood cells in the tube were ruptured and released hemoglobin. At the same time, the absorbance measured by the 96-well plate showed that the hemolysis rate of all experimental groups did not exceed 5%. This result proves that the nanodrug Cur@SA / CMCS-CaCO3 / MnCO3 has excellent blood compatibility. In order to further evaluate the biocompatibility of these nanoparticles in normal tissue cells. Through experiments, we observed the effect of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles on the activity of HUVEC cells in good growth condition. As Figure 2 C shows that after 24 hours of co-incubation with HUVEC cells, the cell survival rate remained above 90% in all experimental groups treated with different concentrations of Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles. This result shows that Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles are almost non-toxic to normal cells, which strengthens their potential as a safe biological carrier material and lays the foundation for their future in vitro and in vivo delivery of anti-tumor nanodrugs. In order to explore the in vitro effect of Cur@SA / CMCS-CaCO3 / MnCO3 on the growth inhibition of HepG2 tumor cells, the CCK-8 method was used to determine the number of viable cells. The results are shown in Figure 2 As shown in Figure D, after 24h of treatment with 0, 5, 10, 15, 25, and 35 μg / mL Cur@SA / CMCS-CaCO3 / MnCO3, the growth inhibition of tumor cells showed a trend related to drug dose, especially when the drug concentration reached above 25 μg / mL, the cell survival rate dropped below 50%, further confirming that the nanodrug system can effectively inhibit the growth of HepG2 cells at a certain concentration. Figure 2As shown in E, from the pictures taken by fluorescence microscope, it can be seen that the HepG2 cells in the PBS group, Cur, CaCO3 / MnCO3 group, SA / CMCS-CaCO3 / MnCO3 group, and Cur@SA / CMCS group showed a healthy growth state. The figure mainly showed green fluorescence and the red fluorescence was almost invisible, indicating that most of the cells in the above five groups survived. It also showed that Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, and Cur@SA / CMCS had very low toxicity to HepG2 cells. However, in the Cur@SA / CMCS-CaCO3 / MnCO3 group, some cell death was observed in the fluorescence field, which was consistent with the results of CCK-8. The reason may be that SA / CMCS-CaCO3 / MnCO3 can help more curcumin to be delivered into the cells, and the synergistic effect of curcumin with calcium and manganese ions promotes the apoptosis of tumor cells. By observing the uptake of nanoparticles in HepG2 cells, the effect of nanodelivery system on the efficiency of drug uptake by tumor cells was explored. Figure 2 F shows the fluorescence microscopy observation results of Cur, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3 after incubation with HepG2 cells for 1, 4 and 6 hours. The results showed that at the same time point, the fluorescence signal in the Cur@SA / CMCS-CaCO3 / MnCO3 treatment group was significantly stronger than that in the free Cur group. This finding proves that the Cur@SA / CMCS-CaCO3 / MnCO3 nanodrug delivery system successfully delivers Cur into tumor cells, and also shows that SA / CMCS-CaCO3 / MnCO3 significantly enhances the tumor cell's ability to take up Cur. After the nanodrug delivery carrier successfully enters the cell, the weakly acidic environment of the lysosome will degrade the delivery carrier molecules and promote the release of calcium ions by the nanodrug delivery carrier. Therefore, the co-localization of calcium ions (green fluorescence) and lysosomes (red fluorescence) in tumor cells after different treatments was observed by fluorescence microscopy, as shown in Figure 2. Figure 2 As shown in G, Cur@SA / CMCS-CaCO3 / MnCO3 nanoparticles successfully released a large amount of calcium ions after entering the cells.
[0058] HepG2 tumor cells were treated with free Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3, respectively, and the untreated group was used as the control to detect the healing of the scratch. Figure 3A shows that after 24 hours, the Cur-treated group and the Cur@SA / CMCS-CaCO3 / MnCO3-treated group significantly inhibited the migration of HepG2 tumor cells; after 48 hours, compared with the control group, the cell migration ability of the Cur@SA / CMCS-CaCO3 / MnCO3-treated group decreased significantly, showing obvious differences. At the same time, when performing cell operations, it can be clearly felt that the ability of cells treated with Cur@SA / CMCS-CaCO3 / MnCO3 to adhere to the culture flask is significantly reduced, and a large number of apoptotic cells and some floating dead cells can be seen in the cell culture medium. These results prove that free Cur can slow down the migration speed of tumor cells, and Cur@SA / CMCS-CaCO3 / MnCO3, with the help of nanoparticle carriers, not only maintains the ability to inhibit migration, but also has an enhanced inhibitory effect compared to simple Cur treatment, further verifying the effectiveness of nanocarriers in enhancing the inhibition of tumor cell migration by chemotherapeutic drugs. Figure 3 As shown in Figure C, after HepG2 tumor cells were treated with Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3, the cell proliferation ability of each group decreased to varying degrees, and the clone formation ability of the Cur@SA / CMCS-CaCO3 / MnCO3 group was even lower, indicating that the drugs loaded by the nanodelivery carrier more effectively inhibited the proliferation of tumor cells.
[0059] like Figure 4 A. After HepG2 tumor cells were treated with Cur and CaCO3 / MnCO3, the results were the same as those of the blank control, and almost no green fluorescence was observed in the cells. However, after treatment with SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS and Cur@SA / CMCS-CaCO3 / MnCO3, ROS were significantly generated. However, the green fluorescence in the cells of the Cur@SA / CMCS-CaCO3 / MnCO3 group was significantly stronger than that of the Cur and SA / CMCS-CaCO3 / MnCO3 groups. It is the nanoparticle carrier that enables curcumin to be taken up more efficiently, and the Fenton-like reaction of manganese ions enhances the generation of more reactive oxygen species ROS to kill tumor cells. This confirms the experimental results of tumor cell uptake of nanoparticles in the previous article. After HepG2 tumor cells were treated with Cur, CaCO3 / MnCO3, SA / CMCS-CaCO3 / MnCO3, Cur@SA / CMCS, and Cur@SA / CMCS-CaCO3 / MnCO3, the cells were stained with JC-1, and CCCP-induced decrease in mitochondrial membrane potential was used as a positive control. Figure 4The red fluorescence of the cells in the control group was stronger, the green fluorescence was slightly stronger in the Cur and Cur@SA / CMCS groups, and the green fluorescence was stronger in the positive control CCCP group and the cells treated with Cur@SA / CMCS-CaCO3 / MnCO3. The above results prove that the treatment with Cur@SA / CMCS-CaCO3 / MnCO3 will lead to a decrease in mitochondrial membrane potential and cause cell apoptosis. In order to explore whether the nanoparticles Cur@SA / CMCS-CaCO3 / MnCO3 can successfully regulate the Ca2+ / -2-hydroxy ... 2+ The Ca content was increased and accumulated in the mitochondria of tumor cells. The Ca 2+ Colocalization with mitochondria. Figure 4 The Ca2+ concentration in the mitochondria of each group of cells after 6 hours of different treatments is shown. 2+ Fluorescence intensity. Ca in the mitochondria of cells in the Cur@SA / CMCS-CaCO3 / MnCO3 group 2+ The fluorescence intensity increased significantly, indicating that the nanoparticles had successfully penetrated into the cells and significantly increased the Ca2+ level in the mitochondria of tumor cells. 2+ This discovery laid an experimental foundation for nanoparticles to interfere with the calcium balance of tumor cells and then induce tumor cells to apoptosis through the mitochondrial pathway.
[0060] Example 4: This example is an in vivo anticancer test on the Cur@SA / CMCS-CaCO3 / MnCO3 nanomaterial prepared in the examples of this application, including the following studies: 1. Establishment of tumor model: HepG2 cells were cultured in a cell culture incubator containing 1% double antibody (100 μL / mL penicillin and 100 mg / mL streptomycin) and 10% FBS at 37° C. and 5% CO 2 . Throughout the process, standard operating procedures were followed.
[0061] The 5-week-old male BALB / c mice (20-25 g) used in this experiment were provided by the Animal Experiment Center of Guangxi Medical University. The mice were housed under constant environmental conditions (room temperature 21±1°C, relative humidity 50-60%, light and dark alternation of 12h / 12h), and all mice had free access to food and water. At the end of the treatment, anesthesia (sodium pentobarbital 40 mg / kg) was used for intramuscular euthanasia. All animal experiments and research projects were approved by the Animal Ethics Committee of Guangxi Medical University (approval number: 202309003).
[0062] HepG2 cells were cultured in DMEM medium with 10% FBS and 1% double antibody at 37°C and 5% CO2. HepG2 cells with good growth and a density greater than 80% were selected, centrifuged and the supernatant was discarded after complete digestion, and an appropriate amount of DMEM was added for resuspending to adjust the cell density to 1×10 7 / ml, and 100μl was inoculated under the armpit of mice to form a HepG2 liver cancer mouse model.
[0063] When the mouse tumor volume grows to 100mm 3 The mice were randomly divided into six groups: PBS, Cur, Cur@CMCS / SA, CaCO3 / MnCO3, CMCS / SA-CaCO3 / MnCO3, and Cur@CMCS / SA-CaCO3 / MnCO3, with 7 mice in each group. Each mouse was injected intratumorally every other day, with an injection dose of 10 mg / kg. After 7 doses according to the grouping, no treatment was given to the mice, and the survival of the mice was observed for 40 days.
[0064] 2. Anti-tumor effect in vivo When the mouse tumor volume grows to 100mm 3 The mice were randomly divided into six groups: PBS, Cur, Cur@CMCS / SA, CaCO3 / MnCO3, CMCS / SA-CaCO3 / MnCO3, and Cur@CMCS / SA-CaCO3 / MnCO3, with 6 mice in each group. Each mouse was treated with intratumoral injection every other day, and the injection dose was 10 mg / kg. Each group of drugs was injected according to the grouping situation, and the whole treatment cycle was 14 days. The weight and tumor volume of the mice were recorded in each treatment. On the 14th day of treatment, the tumor and main organs were collected and weighed, the tumor weight was counted and the organ coefficient was calculated. The formula was: organ coefficient (%) = organ mass / total weight. The main organ sections were subjected to H&E staining. The tumor tissue sections were subjected to H&E staining, TUNEL analysis and Ki-67 staining.
[0065] 3. Anti-tumor mechanism in vivo Calcium salt staining was performed on the tumor tissue sections of the six groups of mice to analyze the tissue calcification, and fluorescent immunohistochemistry was performed to observe the expression of ROS, Bcl-2, Caspase-9 and Cleaved Caspase-3 in tumor tissues. Fresh tumor tissues were then taken to extract proteins and the expression of Bcl-2, Bax, Caspase-9 and Cleaved Caspase-3 proteins in tumor tissues was analyzed by immunoblotting. Mouse serum was taken for enzyme-linked immunosorbent assay to analyze the effect of the material on the expression of proinflammatory factors IL-6 and TNF-α.
[0066] 4. Statistical analysis All quantitative results are expressed as mean ± SD, and for each statistical analysis, the sample size was n ≥ 3. The significant differences in the experimental data were evaluated by one-way analysis of variance (ANOVA). The probability (P) was calculated as *P value < 0.05, **P value < 0.01, and ***P value < 0.001 for significant differences.
[0067] A subcutaneous HepG2 BALB / c mouse model was constructed ( Figure 5 A) During the 14-day treatment, the changes in tumor volume in different groups during treatment Figure 5 As shown in B, the mice in each group were photographed and monitored during the treatment process (as shown in Figure 7 ), and the comparison showed that the tumor growth of Cur@CMCS / SA-CaCO3 / MnCO3 material group was the slowest, which had a certain anti-tumor effect. After the treatment, the subcutaneous tumors of mice in each group were completely removed and photographed ( Figure 5 D), followed by statistical analysis of tumor weight (eg Figure 5 E), consistent with the results of tumor volume changes, the tumor weight of the material group was significantly smaller than that of the other groups. At the same time, there was no abnormal change in the body weight of tumor-bearing BALB / c mice in each group ( Figure 5 C), and weigh the main organs (heart, liver, spleen, lung, kidney) to calculate the organ index ( Figure 5 G), no obvious swelling or degenerative changes were found. The organs of mice in each group were stained with hematoxylin-eosin (H&E) for histological observation, and no obvious acute pathological toxicity and adverse reactions were found in each group ( Figure 8 ). The results of survival curve analysis showed that the survival rate of mice in the Cur@CMCS / SA-CaCO3 / MnCO3 material group could reach more than 50% within 40 days, indicating that Cur@CMCS / SA-CaCO3 / MnCO3 nanomaterials have certain biosafety while having anti-tumor effects.
[0068] The therapeutic effect of Cur@CMCS / SA-CaCO3 / MnCO3 nanomaterials was analyzed by H&E ( Figure 5 H), terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining ( Figure 5 I) and proliferating cell nuclear antigen (Ki-67) staining ( Figure 5J). H&E staining results showed that the cells in the transplanted tumors of the PBS treatment group were significantly heterogeneous, the number of tumor cells in the treatment group decreased, some of them showed nuclear condensation and dissolution, and the cell structure disappeared. In particular, the reduction of malignant tumor cells in the Cur@CMCS / SA-CaCO3 / MnCO3 treatment group was the most obvious, and the tumor killing effect was the most significant. TUNEL staining confocal images showed that the apoptosis signal represented by the green fluorescence co-localized with the cell nucleus was significantly enhanced in the material group. In addition, the tumor cell proliferation signal represented by the Ki-67 staining experiment was significantly decreased. The results of statistical analysis of its fluorescence intensity ( Fig. 9 ) further showed that tumor growth was inhibited, proving the effective tumor therapeutic effect of Cur@CMCS / SA-CaCO3 / MnCO3 nanoparticles.
[0069] Figure 6 A shows that the Cur@CMCS / SA-CaCO3 / MnCO3 treated group had more black deposits compared with the CMCS / SA-CaCO3 / MnCO3 and Cur@CMCS / SA treated groups, indicating that the Cur@CMCS / SA-CaCO3 / MnCO3 nanomaterials with dense calcium shell structure have the ability to stably deliver Ca to tumor tissues. 2+ and had the best calcium overloading effect among all groups under the synergistic effect of curcumin. 2+ The large amount of ROS induced by curcumin exceeds the compensatory level, which will further damage the mitochondria, initiate the mitochondrial apoptosis pathway, and finally induce tumor cell apoptosis. The most commonly used superoxide anion fluorescent detection probe dihydroethidium (DHE) can effectively detect reactive oxygen species. Figure 6 The red fluorescence in the B material group showed the strongest fluorescence signal, and it showed an obvious enhancement trend compared with other groups ( Fig.10 ).
[0070] Figure 6 CE showed that the green fluorescence intensity represented the semi-quantitative status of each protein. The expression of the anti-apoptotic protein Bcl-2 in the control group was significantly down-regulated compared with that in the treatment groups. The expression of the mitochondrial apoptosis pathway initiator Caspase-9 protein and the effector Cleaved Caspase-3 protein were both up-regulated. The fluorescence intensity was statistically analyzed (e.g. Fig.11 ) is consistent with the results shown in the figure. Subsequently, quantitative analysis of each protein (Bcl-2, Bax, Caspase-9 and Cleaved Caspase-3) was performed, and immunoblotting experiments ( Figure 6F) shows that the expression of Bcl-2 protein is down-regulated, while the expression of pro-apoptotic proteins Bax, Caspase-9 and Cleaved Caspase-3, which are antagonistic to Bcl-2, are up-regulated. After quantifying their gray values ( Figure 6 GJ) The trend of the comparison was consistent with the strip results. Then, the mouse serum was subjected to an enzyme-linked immunosorbent assay to observe the effect of Cur@CMCS / SA-CaCO3 / MnCO3 nanomaterials on proinflammatory factors IL-6 and TNF-α ( Figure 6 KL), the results showed that both the Cur@CMCS / SA treatment group and the CMCS / SA-CaCO3 / MnCO3 treatment group had a certain effect of down-regulating the expression of pro-inflammatory factors, but the down-regulation trend of the material group was the most obvious, indicating that it has a certain anti-inflammatory effect and can induce cell apoptosis.
[0071] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A method for preparing composite nanoparticles loaded with curcumin, characterized in that: The steps include: (1) Sodium alginate and chitosan were mixed in a proportion and added into a flat-bottom flask, 200 mL of sodium carbonate solution with a pH of 7.5-8 was prepared and added, and stirred; (2) Then wrap the flat-bottom flask with aluminum foil, add curcumin and stir, and add an appropriate amount of phosphate buffer with pH = 5.8 to adjust the pH of the system in the flask to 7.0; (3) Then, under stirring, 15 mL of calcium chloride solution was added dropwise, followed by slow dropwise addition of 160 μL of manganese chloride solution, while continuing to stir; (4) Then add 7.5 mL of sodium carbonate solution dropwise and continue stirring; (5) The solution in the flat-bottom flask is then centrifuged, the supernatant is discarded, the precipitate is collected, and the precipitate is resuspended in phosphate buffer to prepare a suspension to obtain the composite nanoparticles loaded with curcumin for later use.
2. The preparation method according to claim 1, characterized in that: In step (1), the ratio of sodium alginate to chitosan is 200.0 mg:100.0 mg; the concentration of the sodium carbonate solution is 0.1 mol / L; and the stirring is performed on a magnetic stirrer at 850 rpm for 20 seconds.
3. The preparation method according to claim 1, characterized in that: In step (2), the amount of curcumin used is 1 / 10 of that of chitosan; the stirring is carried out on a magnetic stirrer at room temperature in the dark, and the stirring condition is stirring at 850 rpm for 24 hours.
4. The preparation method according to claim 1, characterized in that: In step (3), the calcium chloride solution and the manganese chloride solution are both added dropwise using a separatory funnel at a flow rate of 1.5 mL / min; the concentration of the calcium chloride solution is 50 mmol / L; and the stirring is performed on a magnetic stirrer at room temperature in the dark at 800 rpm for 4 h.
5. The preparation method according to claim 1, characterized in that: In step (4), the sodium carbonate solution is added dropwise using a 1000 μL single-channel pipette; the solubility of the sodium carbonate solution is 0.1 mol / L; and the stirring is performed on a magnetic stirrer at 800 rpm for 1 hour at room temperature in the dark.
6. The preparation method according to claim 1, characterized in that: In step (5), the centrifugation is performed at 5000 rpm for 10 min in a desktop centrifuge.
7. A composite nanoparticle material loaded with curcumin obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the composite nanoparticle material loaded with curcumin according to claim 7 in preparing a drug for treating liver cancer.
Citation Information
Cited By
Chitin nano drug-loading system and preparation method thereof
CN121943817A
